Phenolic Compounds from Edible Algae: Bioactivity and Health Benefits - Montero, Lidia; del Pilar Sánchez-Camargo, Andrea; Ibáñez, Elena; Gilbert-López, Bienvenida (Current Medicinal Chemistry, 2018)
Algae have been consumed for many years in Asian countries; at present, its consumption around the world either as food ingredient or directly as food commodity has increased considerably mainly due to the Asian influence and its cuisine, but also because of the growing interest in the beneficial health effects of algae. Although several biological activities have been attributed to different algae compounds such as pigments, lipids, polysaccharides, fiber, proteins or vitamins, in the present review we will highlight the different phenolic compounds present on seaweeds and their important role in the functional and health effects, paying special attention to the antioxidant, anti-proliferative, anti-obesity and antidiabetic activities.
Keywords: polyphenols